First, multiply both sides by two to get rid of the 1/2

you're left with:

`20(x+1)=x-18`

Then, distribute the 20 in front of (x+1) and you're left with:

`20x+20=x-18`

then, combine like terms by subtracting 20 from -18 and (1)x from 20x

`19x=-38`

Divide both sides by 19 to get x by itself:

`x=-2`

check:

plug -2 in for x

`20(-2+1)=1/2(-2-18)`

solve:

`10(-1)=1/2(-20)`

`-10=-10`

The first step is to distribute the numbers outside of the parentheses to those inside:

`10(x + 1) = 1/2 (x - 18)`

`10x + 10 = 1/2x - 9`

now move like terms to the same side by adding or subtracting numbers:

`10x - 1/2 x + 10 - 10 = 1/2x - 1/2x - 9 -10`

`10x - 1/2x = -9 - 10`

combine:

9.5 x = -19

now we have to get x alone and 9.5 is in the way and since it is being multiplied by 9.5 we must do the opposite and divide:

`(9.5x)/ 9.5 = -19/9.5`

x = -2

to check:

`10(-2 + 1) = 1/2 (-2 - 18)`

`10 (-1) = 1/2 (-20)`

-10 = -10